Awareness and knowledge of glaucoma among adult ophthalmic patients Attending Central Eye Clinic/Benghazi - J. Elhoni, Safa; A. Bukhatwa , Samar (Benghazi University Medical Journal, 2024)
Background:The risk of blindness caused by glaucoma is higher when individuals lack awareness and understanding of the condition. Delay in the diagnosis of glaucoma is also a significant factor contributing to blindness. The level of awareness of glaucoma in the Libyan population is not known. Aim: to determine the level of glaucoma awareness among Libyans and provide baseline data for better allocation of public health resources. Material and methods:The study was conducted at the Out-Patient Ophthalmology Clinic affiliated with Benghazi Teaching Eye Hospital. Data were collected through a face-to-face interview using a structured questionnaire during the first week of January 2024. The collected data was tabulated, coded, and analyzed using the SPSS program for Windows 7, version 23, and P < 0.05 was considered statistically significant. Results:hundred eighty-five participants were interviewed, with a mean age of 47.8,12.34 (range from 35-80) years. Out of which 156 (84.3%) had heard about glaucoma, but only 32 (17%) were aware of glaucoma based on the study's definition of awareness, 50% were in the age group30-39 years (P= 0.04), 69% were female (P=0.02), 72% were government employees (P=0.04), 91%were not diabetics (P= 0.03)and 47% got their information from family and friends (P<0.001). Regarding knowledge of glaucoma, 34.3% of the aware participants had good knowledge, 59.5% had average knowledge, and 6.2% had poor knowledge. Conclusion: awareness of glaucoma among attendants in the Ophthalmology Clinic Benghazi is low (17%), with half of those aware being in the age group of 30-39 years, with females being more aware than males. The primary source of information for them was family and friends (47%). To address this issue, effective educational campaigns and media strategies are needed to raise awareness levels and prevent blindness caused by glaucoma. WAwareness, Glaucoma, knowledge, blindness, Libya.